Sintesis dan Karakterisasi Biokeramik Tulang sebagai Bahan Implant dengan Metode Sintering - Syamsuddin, Syamsuddin (INTEK: Jurnal Penelitian, 2017)
Abstract—An experimental study on the production of hydroxyapatite (HA = Ca10(PO4)6(OH)2) is conducted in this paper using sintering method. The experiment stars with cleaning process of bovine bone. The final products were characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) and Atomic Absortion Spestroscopy (AAS). The obtained XRD spectra (HA synthesis) were compared to the JCPDS 09-0432 data andis and resulting a good enough result. It is also obtained that HA synthesis rasio Ca/P dengan AAS is 1.69.